The role of dispersed ash in orbital-scale time-series studies of explosive arc volcanism: insights from IODP Hole U1437B, Northwest Pacific Ocean - Corry-Saavedra, Kate; Schindlbeck, Julie Christin; Straub, Susanne M.; Murayama, Masafumi; Bolge, Louise L.; Gómez-Tuena, Arturo; Hashimoto, Yoshitaka; Woodhead, Jon D. (International geology review, 2019)
Tephra fallout beds in marine sediments provide chronologically precise and highly resolved records of volcanism at time scales relevant to Quaternary climate cycles. While the record of discrete (visible) thin tephra beds is readily accessible, the significance of the dispersed (invisible) tephra record remains unclear. Here we evaluate the role of dispersed tephra for orbital-scale volcanic time variations in the Quaternary (<1.2 Ma) carbonate mud of IODP Hole U1437B (Northwest Pacific). The carbonate mud contains cyclic series of discrete fallout tephra beds from the oceanic Izu Bonin ( 85% of tephra beds) and the continental Japan ( 15%) volcanic arcs, respectively. Our results show the inorganic aluminosilicate (lithogenic) fraction is a mixture of dispersed Izu Bonin and Japan ash, and Asian dust. The time distribution of the Izu Bonin ash with its distinct composition appears to confirm and enhance the cyclic time variation of the discrete ash beds at Hole U1437B. Dispersed Japan ash resembles Asian dust in trace elements and is only distinguishable in Sr-Nd isotope space. Collectively, our results confirm the existence of periodic, orbital-scale fluctuations of arc volcanic frequency. Orbital-scale time variations of marine ash may be best established by series of discrete marine ash beds, yet the concomitant dispersed ash flux must also be recorded in order to understand the total flux of arc volcanic ash into the ocean basins and thus the role of the volcanism-climate link.